You need to differentiate the function with respect to x, using product rule and the chaiin rule, such that:

`(u*v) = u'*v + u*v'`

Identifying `u = x^2` and `v = arctan 5x` , yields:

`h'(x) = (x^2)'(arctan 5x) + x^2*(arctan 5x)'`

`h'(x) =2x*arctan 5x + x^2*(1/(1 + (5x)^2))*(5x)'`

`h'(x)...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to differentiate the function with respect to x, using product rule and the chaiin rule, such that:

`(u*v) = u'*v + u*v'`

Identifying `u = x^2` and `v = arctan 5x` , yields:

`h'(x) = (x^2)'(arctan 5x) + x^2*(arctan 5x)'`

`h'(x) =2x*arctan 5x + x^2*(1/(1 + (5x)^2))*(5x)'`

`h'(x) =2x*arctan 5x + (5x)^2/(1 + 25x^2)`

**Hence, evaluating the deirvative of the given function using product rule and chain rule, yields **`h'(x) =2x*arctan 5x + (5x)^2/(1 + 25x^2).`